Effect of Rosemary Cream on Episiotomy Wound Healing in Primiparous Women: A Randomized Clinical Trial - Fatemeh Hadizadeh-Talasaz; Fariba Mardani; Narjes Bahri; Hassan Rakhshandeh; Nasim Khajavian; Marzieh Taghieh (BMC Complementary Medicine and Therapies, 2022)
Abstract Background Delay in episiotomy wound healing can lead to infection. The application of natural antimicrobial agents isolated from herbal essences can be a good strategy to prevent the growth of bacteria and promote the wound healing process. Therefore, this study aimed to determine the effect of rosemary cream on episiotomy wound healing in primiparous women. Methods This triple-blind randomized clinical trial was conducted on 80 primiparous pregnant women who were referred to the maternity ward of Shahid Motahari Hospital in Marvdasht, Iran, from September 2019 to March 2020. These women were randomly assigned into two groups of intervention (rosemary cream) and control (placebo), using variable quadruple blocks. Both groups applied the prescribed cream (in a dose of 2 cm) uniformly on the sutured area to cover it with the cream. The cream was applied twice a day for 10 consecutive days postpartum, and the rate of wound healing was evaluated by the researcher in the first 12 h and at days 4 and 10 postpartum using the REEDA scale. The data were analyzed using SPSS software (Version 19) through the Chi-square test, Mann-Whitney U test, student’s t-test, and Fisher’s test. A p-value less than 0.05 (P < 0.05) was considered statistically significant. Results The mean ± SD REEDA score on the fourth day postpartum was obtained at 3.82 ± 0.93 and 4.25 ± 1.29 in the groups of rosemary cream and placebo, respectively (P = 0.17). However, the mean ± SD REEDA scores on the 10th day postpartum were determined at 0.75 ± 0.74 and 3.32 ± 2.54 in the rosemary cream and placebo groups, respectively, indicating a higher rate of episiotomy wound healing in the group of rosemary cream compared to placebo (P < 0.001). Conclusion Based on the obtained results, it seems that rosemary cream can be effective in healing episiotomy wounds in primiparous women. However, further studies are suggested to confirm the findings of this study. Trial registration This trial was registered in the Iranian Registry of Clinical Trials in 24/08/2019 with the IRCT ID: IRCT20190308042971N1. The first participant enrolled in this trial in September 2019. URL of registry: https://en.irct.ir/trial/40092 .